2020
DOI: 10.1111/hex.13044
|View full text |Cite
|
Sign up to set email alerts
|

‘There is no choice apart from antibiotics…’: Qualitative analysis of views on urinary infections in pregnancy and antimicrobial resistance

Abstract: Background: Antimicrobial resistance (AMR) is a health risk as it can lead to lifethreatening infections. There has been a rise in resistant urinary tract infections (UTIs) which is the most common infection in pregnancy. This can be challenging in pregnancy due to the additional need to safeguard foetal development. The study's aim was to explore views about AMR in women who experienced UTIs in pregnancy. Design: Fifteen semi-structured interviews were conducted in the UK and analysed using thematic analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Two studies looked at those who used clean intermittent self‐catheterization (CISC) 25,26 . Other specific participant groups included pregnant women, 31,32,38 the older population, 27,37 and those with spinal cord injury 28 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies looked at those who used clean intermittent self‐catheterization (CISC) 25,26 . Other specific participant groups included pregnant women, 31,32,38 the older population, 27,37 and those with spinal cord injury 28 …”
Section: Resultsmentioning
confidence: 99%
“…23,24,30,34 Two studies looked at those who used clean intermittent self-catheterization (CISC). 25,26 Other specific participant groups included pregnant women, 31,32,38 the older population, 27,37 and those with spinal cord injury. 28 We extracted 88 concepts from the primary studies and organized these into 34 conceptual categories, further refined into nine themes (Table 4): ( 1) the impact of UTI on my whole body; (2) impact on quality of life, activities, and the associated psychological toll; (3) I know my body and my experience has taught me when I need to seek care; (4) worry and the transition to medicalization; (5) antibiotics are a last resort; (6) Antibiotics are a valuable treatment approach; (7) being heard, seen, and cared for with dignity; (8) self-judgment; and (9) the end of the road, a need for information and cure.…”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies exploring the perceptions of women who experienced UTIs in pregnancy have shown that they were concerned but uncertain on how to tackle antimicrobial resistance [ 36 , 37 ]. One of the studies also showed that while women like to be informed and make decisions for their health, they trust and place high importance on the opinion of the healthcare professional involved in their care [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ghouri et al [13] previously conducted 15 telephone interviews with women with prior documented UTI and described feelings of hopelessness and lack of support in this group. Our study highlights the support experienced by patients with UTI who exchanged information online.…”
Section: Comparison With Prior Workmentioning
confidence: 99%